Compact UWB antenna with sharp tunable band‐notched characteristics. Issue 3 (March 2016) - Li, Tong; Zhu, Cheng; Cao, Xiangyu; Gao, Jun
ABSTRACT: This letter proposes a compact ultra‐wideband antenna with sharp tunable band‐notched function. The antenna utilizes a pair of varactor‐loaded interdigital capacitance loading loop resonators (IDCLLRs) to realize tunable band‐notched characteristics. Compared to many other resonant structures, IDCLLR has a larger effective capacitance, leading to a narrower notch width with a more compact size, thus preventing the waste of useful spectrum. The varactors are independently controlled to achieve single or dual notched bands, and the notch frequencies can be electronically tuned by varying the bias voltages across the varactors. Measured results are in good agreement with the simulations, which demonstrates that the proposed antenna can easily adapt to the changeable environment. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:529–532, 2016